Climate mobility to Europe: The case of disaster displacement in Austrian asylum procedures - Mayrhofer, Monika; Ammer, Margit (Frontiers in Climate, 2022)
Disaster displacement is an increasing challenge in the context of climate change. However, there is a lack of research focusing on Europe as a destination area, including on the question how the normative protection gap with regard to cross-border disaster displacement is addressed from a European perspective. Against this background this article provides evidence from a European case study focusing on the role of disaster, such as droughts or floods, in asylum procedures in Austria. Based on a qualitative content analysis of 646 asylum decisions rendered by the Austrian appellate court (supplemented by qualitative interviews with relevant Austrian stakeholders), it is demonstrated that disasters are—to a certain extent—already taken into consideration in Austrian asylum procedures: impacts of disasters are not only brought forward by applicants for either leaving the country of origin or for not wanting or not being able to return. They are also increasingly discussed in the legal reasoning of judgments of the Austrian appellate court. The analysis shows that impacts of disasters play an important role mainly in decisions concerning persons from Somalia, and here primarily in the assessment of the non-refoulement principle under Article 3 ECHR and subsidiary protection. This can be regarded as a response to the protection gap—even though not necessarily applied consistently.